La scolarisation et la formation professionnelle comme voies d’intégration des grands adolescents immigrants - Eva Lemaire (Cahiers de la Recherche sur l'Education et les Savoirs)
School is supposed to be one of the greatest ways to integrate teenagers that have just emigrated in France. This paper will assert the problem of the place of schooling in the career of young first generation migrants, the so-called “unaccompanied children” whose right to stay depends on their integration and their academic achievements. After examining the question of the access of those migrants to the French school system, this article will analyse the context in which the schooling of these unaccompanied children is fixed: it is a context of social instability but also a political context, lying on the refusal of a “non chosen” immigration. It is the first survey that analyses what these young migrants become. This paper is relying on a cohort study realised on a period of four years and on a series of interviews of former unaccompanied children, in order to determine the nature of their academic development, between achievements and multiple ruptures.